Pemberdayaan Kelompok Wanita Tani (KWT) Melalui Program Makan Gratis Sebagai Solusi Stunting - Lulu Luthfiyah; Riah Ngenaeby Kembaren; Junil Adri; Gita Rayna Dinata; Firda Nathania Maheswari; Rhabila Chandra Yuanda; Taufiqul Israt; Ronaldo Barus (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Stunting is one of the chronic nutritional problems that is still a challenge in Indonesia. Lack of balanced nutritional intake from pregnancy to toddler age is the main factor causing it. In an effort to overcome stunting, the government has initiated the Free Meal Program as a strategy to increase nutritional intake for vulnerable groups. One important element in supporting the success of this program is the role of the Women Farmers Group (KWT), which plays a role in providing nutritious local food through land utilization. This research was conducted in Nagari Sungai Duo, Sitiung District, Dharmasraya Regency, West Sumatra, using descriptive methods and a participatory approach. Activities included nutrition and stunting counseling, land cleaning and optimization, and planting corn seeds as the main food source in the free meal program. The results showed that nutrition education increased public awareness of the importance of consuming nutritious food, while land optimization by KWT increased the availability of local food. Planting corn as part of a food security strategy contributed to supporting the free meal program and reducing stunting rates in the area.